2012
DOI: 10.1021/jf204434t
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Sodium Release and Saltiness Perception in Solid Lipoprotein Matrices. 1. Effect of Composition and Texture

Abstract: Reducing the sodium content in foods is complex because of their multidimensional sensory characteristics and the multifunctionality of sodium chloride. The aim of this study was to elucidate how food composition may influence in-mouth sodium release and saltiness perception. Lipoprotein matrices (LPM) were produced using milk constituents and characterized by means of rheological measurements, texture, and taste sensory profiles. Texture and taste perceptions were affected differently by variations in the sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 39 publications
7
47
1
Order By: Relevance
“…By increasing the amount of fat in a food matrix, hydrophilic water soluble molecules are “pushed” into the aqueous phase increasing their relative concentration. This may increase the perceived intensity of the flavor (Chabanet et al , 2013; Lawrence et al , 2012). Similarly volatiles with low fat solubility (lipophobic molecules) may be released faster in the presence of significant levels of fat (Frank, 2015).…”
Section: Fat and Beef Flavormentioning
confidence: 99%
“…By increasing the amount of fat in a food matrix, hydrophilic water soluble molecules are “pushed” into the aqueous phase increasing their relative concentration. This may increase the perceived intensity of the flavor (Chabanet et al , 2013; Lawrence et al , 2012). Similarly volatiles with low fat solubility (lipophobic molecules) may be released faster in the presence of significant levels of fat (Frank, 2015).…”
Section: Fat and Beef Flavormentioning
confidence: 99%
“…Strategies to optimize product structures for enhanced saltiness include the acceleration of the dissolution rate of salt crystals from dry products using very fine crystals (Kilcast & den Ridder, 2007), the use of inert fillers to concentrate salt in the aqueous phase (Goh, Leroux, Groeneschild & Busch, 2010), and the adaptation of food matrix composition. For example, a higher water content led to a faster sodium release and a higher fat content led to a decreased saltiness perception in solid lipoprotein matrices (Lawrence et al, 2012a;Lawrence, Septier, Achilleos, Courcoux & Salles, 2012b). Furthermore, a faster sodium release during mastication was associated with an intense salty taste in bread crumbs (Konitzer, Pflaum, Oliveira, Arendt, Koehler & Hofmann, 2013;Pflaum et al, 2013b) and in polysaccharide model systems (Scherf, Pflaum, Koehler & Hofmann, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, in-mouth salt release and saltiness perception depend on both food characteristics and oral parameters. [24][25][26] In particular, fat influenced in-mouth salt release and saltiness perception differently depending on the fat level. [24][25][26] In particular, fat influenced in-mouth salt release and saltiness perception differently depending on the fat level.…”
Section: Introductionmentioning
confidence: 99%
“…13 It was reported that the combined effects of food composition and chewing behaviour affected salt release in model cheeses. 26 Moreover, most people develop an individual oral strategy consisting of an adaptation of oral behaviour to the food characteristics. 26 Moreover, most people develop an individual oral strategy consisting of an adaptation of oral behaviour to the food characteristics.…”
Section: Introductionmentioning
confidence: 99%